Simulation-Based Defect Engineering in “α-Spodumene” - Sivanujan Suthaharan; Poobalasuntharam Iyngaran; Navaratnarajah Kuganathan (ChemEngineering, 2021)
Naturally occurring lithium-rich α-spodumene (α-LiAlSi2O6) is a technologically important mineral that has attracted considerable attention in ceramics, polymer industries, and rechargeable lithium ion batteries (LIBs). The defect chemistry and dopant properties of this material are studied using a well-established atomistic simulation technique based on classical pair-potentials. The most favorable intrinsic defect process is the Al-Si anti-site defect cluster (1.08 eV/defect). The second most favorable defect process is the Li-Al anti-site defect cluster (1.17 eV/defect). The Li-Frenkel is higher in energy by 0.33 eV than the Al-Si anti-site defect cluster. This process would ensure the formation of Li vacancies required for the Li diffusion via the vacancy-assisted mechanism. The Li-ion diffusion in this material is slow, with an activation energy of 2.62 eV. The most promising isovalent dopants on the Li, Al, and Si sites are found to be Na, Ga, and Ge, respectively. The formation of both Li interstitials and oxygen vacancies can be facilitated by doping of Ga on the Si site. The incorporation of lithium is studied using density functional theory simulations and the electronic structures of resultant complexes are discussed.